Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. The degree of availability of professional digital skills in the performance of faculty members at The University of Hail From their point of view Co-Prof. Hatouf Farah Samara, Asst-Prof. Ahlam Ibrahim M. Alhaj Hussein , Asst-Prof. Ghada Alameen Ahmed Suliman , Asst-Prof. Ahlam Elimam Abdalla Yousif 2. Teaching mathematics remotely for the elementary level: Challenges and recommendations for development from the teachers viewpoint Mr. Thamer Nawaf Alrashdi 3. An analytical study of contemporary educational issues contained in the websites of educational research and studies centers Mr. Mohammed Maudud, Mr. Souleyman Diallo , Dr. Abdulrahman Mohammed N. Alharthi 4. Attitudes of Female Master’s students in Instructional Technology Program at Najran University towards the Use of Augmented Reality Technology Mrs. Shroug Mesali Saleh Alyami 5. The level of satisfaction of psychological needs based on the realistic model and its relationship to psychological happiness among An-Najah National University students Mrs. Mays Majed Kahla, Dr. Filasteen Ismail Nazzal 6. The reality of primary school teachers’ use of educational games in teaching mathematics Mrs. Afrah Essa Al-Najei 7. Reflections of Teachers’ Participation in the eTwinning platform on Their Professional and Personal Development in Jordan Dr. Njoud Yousuf Alananbeh